Neuromuscular, Biochemical, Endocrine, and Mood Responses to Small-Sided Games' Training in Professional Soccer. Issue 9 (September 2018) - Sparkes, William; Turner, Anthony; Weston, Matthew; Russell, Mark; Johnston, Michael; Kilduff, Liam
Abstract : Abstract: William, S, Turner, AN, Weston, M, Russell, M, Johnston, MJ, and Kilduff, LP. Neuromuscular, biochemical, endocrine, and mood responses to small-sided games' training in professional soccer. J Strength Cond Res 32(9): 2569–2576, 2018—The 24-hour responses to small-sided games' (SSGs) soccer training were characterized. Professional soccer players ( n = 16) performed SSG's (4vs4 + goalkeepers; 6 × 7-minutes, 2-minute interset recovery) with performance (peak power output [PPO] and jump height [JH]), physiological (blood creatine kinase [CK], lactate, salivary testosterone, and cortisol), and mood measures collected before (baseline), and after (immediately; 0, +2, and +24 hours). For PPO and JH, possibly small-moderate reductions occurred at 0 hour (−1.1 W·kg −1 ; ±0.9 W·kg −1, −3.2 cm; ±1.9 cm, respectively), before returning to baseline at +2 hours (trivial), and declining thereafter (small-moderate effect) at +24 hours (−0.9 W·kg −1 ; ±0.8 W·kg −1, −2.5 cm; ±1.2 cm, respectively). Lactate increased at 0 hours (likely large; +1.3 mmol·L −1 ; ±0.5 mmol·L −1 ), reduced at +2 hours (likely-small; −0.5 mmol·L −1 ; ±0.2 mmol·L −1 ), and returned to baseline at 24 hours (trivial). A very likely small increase in CK occurred at 0 hour (+97 μ·L −1 ; ±28 μ·L −1 ), persisting for +24 hours (very likely small; +94 μ·L −1 ; ±49 μ·L −1 ). Possibly small increases in testosterone (+20 pg·ml −1 ; ±29 pg·ml −1 ) occurred at 0 hour, before likely moderate declines at +2 hours (−61 pg·ml −1 ; ±21 pg·ml −1 ) returning to baseline at +24 hours (trivial). For cortisol, possibly small decreases occurred at 0 hour (−0.09 μg·dl −1 ; ±0.16 μg·dl −1 ), before likely large decreases at +2 hours (−0.39 μg·dl −1 ; ±0.12 μg·dl −1 ), which persisted for 24 hours (likely small; −0.12 μg·dl −1 ; ±0.11 μg·dl −1 ). Mood was disturbed by SSG's at 0 hour (likely moderate; +13.6 AU, ±5.6 AU) and +2 hours (likely small; +7.9 AU; ±5.0 AU), before returning to baseline at +24 hours (trivial). The movement demands of SSG's result in a bimodal recovery pattern of neuromuscular function and perturbations in physiological responses and mood for up to 24 hours. Accordingly, when programming soccer training, SSG's should be periodized throughout the competitive week with submaximal technical/tactical activities.